Open data and co-production of public value of BBC Backstage. (1st June 2015) - Lin, Yuwei
Openly accessible data sets (open data) have been recognized as valuable assets for creating business opportunities, revitalizing innovation and transparentizing organizational conducts. Public Service Broadcasters (PSB) such as the British Broadcasting Corporation (BBC) have been motivated to experiment with open data and new forms of innovation in content making, delivery and audience engagement. Through a case study of the BBC Backstage project, this article examines how such open innovation processes of engaging the public in the reuse and remix of open data were conceived, supported, managed and maintained. The research found that BBC Backstage had played an important role in encouraging and motivating people to reuse and repurpose the open data released by the BBC. New forms of outputs have emerged, as seen in the Data Arts visualization project and the R&DTV clips mashups. The article argues that PSB public value can be co-produced through opening up data sets, encouraging reuse and remix, and building up a network of enthusiastic and capable active audiences, the techno-elites, whose status has been encouraged the open data culture and alike. Lessons learned can help understand the meanings of open data from the PSB perspective, and the implications in media industry thereby foster innovation in future media and creative industries.